Study on Image Calibration Method in Automatic Meteorological Observation of Crops. Issue 4 (December 2018) - Li, Yimin; Tian, Dongzhe; Li, Xinge; Xu, Ge; Tian, Zengguo
Abstract: The digital camera was used to collect crop real scene images in automatic observation of crop meteorology, and image processing algorithm was used to extract crop characteristics. Due to the influence of camera distortion parameters, the real images have distortion in different degrees, and there are deviations in the recognition results of the observed area, density and incubation period. According to the results of the crop automatic identification, contrast the distortion parameters of camera was analyzed, and the camera calibration algorithm is studied. Moreover, the accuracy of crop automatic observation was improved, due to the image correction.